The End of the Robinson-Patman Act? Evidence from Legal Case Data - Luchs, Ryan; Geylani, Tansev; Dukes, Anthony; Srinivasan, Kannan (Management Science, 2010)
The Robinson-Patman Act (RP), an antitrust statute aimed at protecting small businesses, limits price setting in distribution channels. To avoid costly penalties under RP, managers take a variety of precautions when pricing to retailers and wholesalers. But how likely is a court to find a defendant guilty of violating the RP? We find that this likelihood has dropped drastically as a result of recent Supreme Court rulings from more than 1 in 3 before 1993 to less than 1 in 20 for the period 2006–2010. The analysis also points to an increased success of the no harm to competition defense, which reflects the view that the courts have raised the hurdle for plaintiffs to establish competitive harm. Finally, our results indicate that smaller plaintiffs over time have fared worse than larger ones, a trend that challenges the notion that RP protects small businesses.